Drishti : Real-Time Object Recognition for the Visually Impaired - Parekh, Hitanshu; Agarwal, Niyati; Bangera, Pranav; D’souza, Roger; Tuscano, Grinal (Indian Journal of Computer Science, 2023)
In 2017, the World Health Organization (WHO) reported that nearly 284 million individuals worldwide experienced some degree of visual impairment, with approximately 39 million individuals suffering from total blindness. People with visual impairments often rely on assistance from others or use canes to move around and identify obstacles. Our proposed system aims to aid the visually impaired by identifying and classifying common objects in real-time, as well as recognizing text from various sources such as documents and signs. This system provides voice feedback to enhance understanding and navigation, and utilizes depth estimation algorithms to determine a safe distance between objects and individuals, promoting self-sufficiency and reducing dependence on others. We employ the COCO image dataset, which contains everyday objects and people, and utilize the Mobilenet SSD algorithm for real-time object identification. To enable real-time Optical Character Recognition (OCR) Text-To-Speech functionality, we employ advanced technologies such as OpenCV, Python, and Tesseract for text detection and recognition, and the Pyttsx3 library for converting recognized text into audible speech. Our proposed system is dependable, affordable, realistic, and feasible.